Predictors of severe outcome following opioid intoxication in children. (3rd June 2022) - Cohen, Neta; Mathew, Mathew; Davis, Adrienne; Brent, Jeffrey; Wax, Paul; Schuh, Suzanne; Freedman, Stephen B.; Froberg, Blake; Schwarz, Evan; Canning, Joshua; Tortora, Laura; Hoyte, Christopher; et al.
Abstract: Introduction: While the opioid crisis has claimed the lives of nearly 500, 000 in the U.S. over the past two decades, and pediatric cases of opioid intoxications are increasing, only sparse data exist regarding risk factors for severe outcome in children following an opioid intoxication. We explore predictors of severe outcome (i.e., intensive care unit [ICU] admission or in-hospital death) in children who presented to the Emergency Department with an opioid intoxication. Methods: In this prospective cohort study we collected data on all children (0–18 years) who presented with an opioid intoxication to the 50 medical centers in the US and two international centers affiliated with the Toxicology Investigators Consortium (ToxIC) of the American College of Medical Toxicology, from August 2017 through June 2020, and who received a bedside consultation by a medical toxicologist. We collected relevant demographic, clinical, management, disposition, and outcome data, and we conducted a multivariable logistic regression analysis to explore predictors of severe outcome. The primary outcome was a composite severe outcome endpoint, defined as ICU admission or in-hospital death. Covariates included sociodemographic, exposure and clinical characteristics. Results: Of the 165 (87 females, 52.7%) children with an opioid intoxication, 89 (53.9%) were admitted to ICU or died during hospitalization, and 76 did not meet these criteria. Seventy-four (44.8%) children were exposed to opioids prescribed to family members. Fentanyl exposure (adjusted OR [aOR] = 3.6, 95% CI: 1.0–11.6; p  = 0.03) and age ≥10 years (aOR = 2.5, 95% CI: 1.2–4.8; p  = 0.01) were independent predictors of severe outcome. Conclusions: Children with an opioid toxicity that have been exposed to fentanyl and those aged ≥10 years had 3.6 and 2.5 higher odds of ICU admission or death, respectively, than those without these characteristics. Prevention efforts should target these risk factors to mitigate poor outcomes in children with an opioid intoxication.